Analisa Performansi Jaringan Telekomunikasi Fiber to the Home (FTTH) Menggunakan Metode Power Link Budget Pada Kluster Bhumi Nirwana Balikpapan Utara - Amalia Rizqi Utami; Della Rahmayanti; Zafira Azyati (PTE FTK UIN Ar-Raniry, 2022)
Currently, the technology needed in the era of digitalization is increasing rapidly. Especially, the need of an internet network. During this pandemic, which requires people to carry out their activities from home or known as Work From Home (WFH). In order to support the success of WFH activities, an adequate internet connection is required. Based on these problems, this study was conducted to analyze the performance of the Fiber to the Home (FTTH) telecommunications network in the Bhumi Nirwana Cluster, Batu Ampar, North Balikpapan. The analysis technique chosen designed a simulation using OptiSystem software and mathematical calculations using the Power Link Budget method. After a sessions of experiments and mathematical calculations, it can be concluded that the Bit Error Rate (BER) value obtained is categorized as